Co-participation in the Swiss water forum network*. Issue 3 (4th May 2019) - Fischer, Manuel; Angst, Mario; Maag, Simon
Abstract: In polycentric governance systems, actors interact in different venues, such as forums which foster cross-sectoral interaction. This analysis centres on water forums in Switzerland and on actors with multiple forum memberships, creating interactions throughout the entire forum network. Findings show that the central actors in the entire water forum network are predominantly from the public administration sector, even though members from the private sector are most numerous. Despite an emphasis on the bottom-up and self-organizing character of polycentric governance systems in the literature, this analysis shows that public administration actors still play a crucial role as network managers and brokers.